2011
DOI: 10.1074/jbc.m111.244889
|View full text |Cite
|
Sign up to set email alerts
|

Specific and Modular Binding Code for Cytosine Recognition in Pumilio/FBF (PUF) RNA-binding Domains

Abstract: Pumilio/fem-3 mRNA-binding factor (PUF) proteins possess a recognition code for bases A, U, and G, allowing designed RNA sequence specificity of their modular Pumilio (PUM) repeats. However, recognition side chains in a PUM repeat for cytosine are unknown. Here we report identification of a cytosine-recognition code by screening random amino acid combinations at conserved RNA recognition positions using a yeast three-hybrid system. This C-recognition code is specific and modular as specificity can be transferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
140
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(145 citation statements)
references
References 34 publications
4
140
0
Order By: Relevance
“…By linking a modified PUF to an effector domain, regulation can be targeted to specific mRNAs (39)(40)(41). The plasticity of interactions reported here raises considerations for such studies: Flexibility may cause off-target effects.…”
Section: Discussionmentioning
confidence: 99%
“…By linking a modified PUF to an effector domain, regulation can be targeted to specific mRNAs (39)(40)(41). The plasticity of interactions reported here raises considerations for such studies: Flexibility may cause off-target effects.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that our individual PPR modules can be combined within the engineered cPPR proteins with the capacity to modify their binding specificities to single-nucleotide level, providing further evidence of their modularity. We thus demonstrate that they might be engineered to target and manipulate RNAs of interest, as has been the case for PUFs 7,26,37,[39][40][41][42][43][44][45][46] . Here we focused on engineered proteins with eight PPRs.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we have manipulated cytoplasmic events, including translation and changes in poly(A) length. Two reports recently used a similar strategy to control pre-mRNA splicing in the nucleus, engineering PUF proteins to cause shifts in splicing patterns (19,47). In those cases, the effector domain was derived from an SR-or G-rich protein, and activated or repressed splicing, respectively.…”
Section: A Hs Pum1mentioning
confidence: 99%